Effect of cytisine on some brain and hepatic biochemical parameters in spontaneously hypertensive rats - Simeonova, Rumyana (Slovak Toxicology Society SETOX, 2010)
Tobacco smoking is a risk factor for variety of cardio-vascular diseases, such as hypertension, myocardial infarction, stroke and many others. It is of great importance for hypertensive patients to stop smoking. One of the medicines widely used for smoking cessation in Bulgaria is the original Bulgarian product Tabex®, which is developed on the basis of natural plant alkaloid cytisine. The aim of the following study was to ivestigate the effects of cytisine on some brain and hepatic biochemical parameters in spontaneously hypertensive rats (SHR), an widely used rodent model for human essential hypertension, and to compare the obtained results with their age-matched normotensive controls Wistar Kyoto (WKY). Multiple cytisine administration did not affect the activity of ethylmorphine-N-demethylase (EMND) and anylinehydroxylase (AH), as well as the quantity of cytochrome P 450, nor in WKY neither in SHR In the liver cytisine increased the MDA quantity both in SHR and in WKY, by 25% (p<0.05) and by 29% (p<0.05) respectively, while the GSH level was not significantly changed by the compound in both strains. In contrast, on the brain level, cytisine administration to SHR caused more prominent toxicity, resulted in GSH depletion and increased MDA quantity, while in WKY strain did not exert any toxicity. Cytisine did not significantly affect ALAT and ASAT activity in both strains. In conclusion, the results of our study suggest higher brain toxicity of cytisine in spontaneously hypertensive rats, that might be due to their pathophysiological characteristics.